Thermoelectrics and its energy harvesting - Rowe, David Michael (CRC Press, 2012)
"This book includes updated theoretical considerations which provide an insight into avenues of research most likely to result in further improvements in material performance. It details the latest techniques for the preparation of thermoelectric materials employed in energy harvesting, together with advances in the thermoelectric characterisation of nanoscale material. The book reviews the use of neutron beams to investigate phonons, whose behaviour govern the lattice thermal conductivity and includes a chapter on patents"--